Islam Populer sebagai Pencarian Identitas Muslim Kelas Menengah Indonesia - Wasisto Raharjo Jati (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2015)
This article aims to analyze the construction of identity in the case study of Middle-Class Muslim in Indonesia. The term “Popular Islam” is part of an academic term to make Islam an identity for the Middle-Class Muslim in Indonesia. This term can be interpreted into two premises: popular Islam as a commoditization of Islamic value and Islam as part of the celebration of Islamic day. These terms later then forked between Islamization and indigenization, thus creating their assorted shades of Middle-Class Muslims in Indonesia. Consumption then presents a cultural sign to distinguish the Middle Class. It was later manifested in the mass cultural products on behalf of Islam. That image displayed on consuming the product and then create a construction of an Islamic Middle Class, religious Middle Class, and the Arabized Middle Class. This paper will elaborate more deeply about searching for identity and its impact on Middle-Class Muslims in Indonesia.